Cost effectiveness of focal impulse and rotor modulation guided ablation added to pulmonary vein isolation for atrial fibrillation. (7th March 2018) - Baykaner, Tina; Duff, Steve; Hasegawa, James T.; Mafilios, Michael S.; Turakhia, Mintu P.
Abstract: Background: Although ablation with focal impulse and rotor modulation (FIRM), as an adjunct to pulmonary vein isolation (PVI), has been shown to decrease atrial fibrillation (AF) recurrence, cost‐effectiveness has not been assessed. Objective: We aimed to evaluate the cost effectiveness of FIRM‐guided ablation when added to PVI in a mixed AF population. Methods and results: We used a Markov model to estimate the costs, quality‐adjusted survival, and cost effectiveness of adding FIRM ablation to PVI. AF recurrence rates were based on 3‐year data from the CONFIRM trial. Model inputs for event probabilities and utilities were obtained from literature review. Costs were based on Medicare reimbursement, wholesale acquisition costs, and literature review. Three‐year total costs FIRM+PVI versus PVI alone were $27, 686 versus $26, 924. QALYs were 2.338 versus 2.316, respectively, resulting in an incremental cost‐effectiveness ratio (ICER) of $34, 452 per QALY gained. Most of the cost (65–81%) was related to the index ablation procedure. Lower AF recurrence generated cost offsets of $4, 266, primarily due to a reduced need for medications and repeat ablation. Probabilistic sensitivity analysis demonstrated ICER below $100, 000/QALY in 74% of simulations. Conclusion: Based on data from the CONFIRM study, the addition of FIRM to PVI does have the potential to be cost‐effective due to higher quality‐adjusted life years and lower follow‐up costs. Value is sensitive to the incremental reduction in AF recurrence, and FIRM may have the greatest economic value in patients with greater AF symptom severity. Results from ongoing randomized trials will provide further clarity.